Management by Shoura (MBS) / Norlaila Abdullah - Abdullah, Norlaila (Universiti Teknologi MARA Cawangan Pahang, 2005)
The Management By Shoura is a model, which blends two schools of thoughts: the Qur'anic chapter of Al-shoura and the worldly concept of strategic management. It aims to illustrate the Al-Shoura revelation in the Holy Qur'an and the worldly managerial system of governance. Likewise, it highlights the importance of practicing Al-Shoura principles in the daily lives of the believers, its rewards, and benefits. In the context of worldly task, faith and work values have close linkage: Al-Shoura principles permeate in the daily work activities of any worldly-wise Ummah, whose vision is to seek more endowments now and thereafter. Strategically speaking, this concept shows the attributes of shoura team composition, its member's attitudes, its dimensional focus, assistance provided to rank in file employees and shoura conflict management. This further envisages to combining the Ummah's appreciation to the revelation of Allah, the Al-Mighty and the Sunnah of the Prophet Muhammad, peace be upon him, into one's daily assignment making him become more responsible.